Atlantic‐Origin Cold Saline Water Intrusion and Shoaling of the Nutricline in the Pacific Arctic - Jinyoung Jung; Kyoung‐Ho Cho; Taewook Park; Eri Yoshizawa; Youngju Lee; Eun Jin Yang; Jong‐Ku Gal; Sun‐Yong Ha; Soobin Kim; Sung‐Ho Kang; Jacqueline M. Grebmeier (Geophysical Research Letters)
Abstract Atlantic‐origin cold saline water has previously not been considered an important contributor to the nutrient supply in the Pacific Arctic due to the effective insulation by the overlying Pacific‐origin waters that separate the surface mixed layer from the deeper Atlantic Water. Based on hydrographic observations in the northwestern Chukchi Sea from 2015 to 2017, we demonstrate that the intrusion of Atlantic‐origin cold saline water into the halocline boundary between Pacific and Atlantic‐origin waters in 2017 lifted Pacific‐origin nutrients up to the surface layer. We find that the cyclonic atmospheric circulation in 2017 was considerably strengthened, leading to lateral intrusions of two bodies of cold halocline water from the Eurasian marginal seas into the northwestern Chukchi Sea. Our results reveal that the intrusions of cold halocline waters caused unprecedented shoaling of the nutricline and anomalously high surface phytoplankton blooms in typically highly oligotrophic surface waters in the region during summer.